The central lymph node dissection using carbon nanoparticle in transoral vestibular approach endoscopic thyroid surgery - Hui Li; Zeyang Liu; Wu Li (Scientific Reports)
Abstract This research seeks to explore the application value of carbon nanoparticle (CN) in transoral endoscopic thyroidectomy vestibular approach (TOETVA) with the goal of providing more reliable clinical evidence for minimally invasive treatment of thyroid cancer.A total of 110 patients with differentiated thyroid cancer (DTC) met the inclusion and exclusion criteria from September 2019 to January 2020. They were divided into an experimental group (TOETVA group) of 80 patients and a control group (OT group) of 30 patients based on their cosmetic preferences. All patients were treated with CN during surgery, and the surgeon actively selected lymph nodes and sent them separately for examination according to < 5 mm (small) and ≥ 5 mm (large), recording the number of row retrieved lymph nodes (RRLN). Routine medical examination was conducted to report the number of retrieved lymph nodes (RLN) and positive central lymph nodes (PLNs) detected one week after surgery. The positive rate (PR) of lymph nodes and the proportion of lymph node positive individuals were calculated. Compared with the control group, there was no significant difference between the experimental group and the control group in the proportion of RRLN, RLN, PLN, PR, and lymph node positivity. The differences in the number of lymph nodes of the same group: small lymph nodes have more RRLN and RLN than large lymph nodes, and the difference is statistically significant. In the experimental group, RRLN is larger than RLN, the difference is statistically significant. There is a slight difference between the control group and the experimental group, RRLN is generally higher than RLN. The lymph node clearance effect of TOETVA and OT is basically consistent. The use of CN can improve the detection rate of small lymph nodes in TOETVA, and it is recommended to use CN during the procedure.